The Impact of Differentiated Learning, Adversity Intelligence, and Peer Tutoring on Student Learning Outcomes - Nur Hidayat; Yayat Ruhiat; Nurul Anriani; Suryadi Suryadi (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Differentiation is a well-recognized strategy that assists teachers in addressing the needs of students with varying abilities in a classroom of students with different characteristics. The research investigates the impact of differentiation learning, adversity intelligence, and peer tutoring on student learning outcomes. Method: This research employs a statistical survey approach to guarantee outcome accuracy. The researchers employed a partial least squares-structural equation model (PLS-SEM) to determine the values of latent variables to make predictions. The questionnaire was used as the data-gathering tool in this study. The investigation occurred at a vocational high school in Serang Regency in Banten Province, Indonesia. Were 250 students in the vocational high school in Serang Regency, Indonesia. The sampling procedure was conducted using a random approach. Results: The statistical study of the structural model indicates a considerable positive link between differentiated learning and adversity intelligence. Adversity intelligence and peer tutoring were positively correlated. Differentiated learning is positively correlated with learning outcomes. Learning outcomes are positively correlated with peer tutoring. Novelty: This research presents novelty research that combines differentiated learning, adversity intelligence, and peer tutoring to examine their impact on student learning outcomes. This research is novel in its attempt to incorporate multiple variables into a single unit for investigation and exploration. This research is intriguing due to variations in emphasis, research participants, and incorporation of research factors compared to earlier studies.